The Effect of Compensation Management on Employee Retention Among Street Vendors in Pangkalpinang with Entrepreneurial Orientation as a Mediating Variable - Luthfi Darma Saputra; Eva Agus Rusdiana; Juhari Juhari (Asosiasi Peneliti dan Inovasi Nusantara (APIN), 2026)
This study analyzes the effect of compensation management on employee retention among street vendors in Pangkalpinang, with an entrepreneurial orientation as a mediator. The informal sector experiences high turnover due to traditional and unstructured compensation systems. This quantitative study involved 96 street vendors with PLS-SEM analysis using SmartPLS 4.0. The results show: (1) Compensation management has a significant positive effect on entrepreneurial orientation (β=0.729, p<0.001); (2) Compensation management does not have a significant direct effect on retention (β=0.035, p=0.827); (3) Entrepreneurial orientation has a significant positive effect on retention (β=0.760, p<0.001); (4) Entrepreneurial orientation fully mediates the effect of compensation on retention (94% of the effect is mediated, indirect effect=0.554, p<0.001). The findings indicate that improving retention requires a holistic approach that combines a structured compensation system with the development of an entrepreneurial culture. The study contributes to the HRM literature in the informal sector, showing that HRM practices remain relevant with different mechanisms from the formal sector.